An Investigation On The Coupled Gas-Solid Reactions Using Matlab- Nickel Oxide Reduction By Carbon - Lim, Ze En (Universiti Sains Malaysia, 2017)
Nickel is an important industrial catalyst and has several important applications. Thus, it is important to discover a simpler and more effective reductive process to produce nickel. In this study, nickel oxide reduction by carbon is performed experimentally using Design of Experiment (DOE) in variation of parameters. The parameters studied are reduction temperature (800oC to 1000oC), reduction time (1 hour to 2 hours) and molar ratio of C to NiO (0.5 to 1.5). Shrinking core model for isothermal and non-isothermal conditions is employed using MATLAB programming for the kinetic modelling of reduction process to determine the extent of reduction and the reaction rate. The models are developed from independently measured physical and thermodynamic properties of the reaction system, and experimentally measured properties. The predicted extent of reduction is then compared with the experimentally measured results. From the DOE analysis, as compared to other parameters, reduction time shows most significant effect on the percentage of weight reduction and extent of reduction. SEM and XRD analysis are also done to ensure the reduction process has taken place effectively. From the study, the extent of reduction increases with increasing reduction temperature, reduction time and molar ratio of C to NiO. The highest extent of reduction in this study is 77.88%, which is achieved at reduction temperature of 1000oC, 2 hours of reduction time and molar ratio of C to NiO at 1.5. From the result of kinetic modelling, both isothermal and non-isothermal shrinking core model show similar trend and significant closeness to the experimental result.